Swainson's handbook of technical and quality management for the food manufacturing sector - Swainson, M. (Woodhead Publishing, an imprint of Elsevier, 2019)
This book is focused on the expansive and highly demanding subject of Food Industry "Technical & Quality Management". As the world's most vital industry "Food Production" is complex, multifaceted and continuously scrutinised. Food scares and product recalls, on national and international scales, demonstrate the persistent challenge to identify, monitor and control all hazards, and also address the increasing criminal threats of Food Fraud, Adulteration & Intentional Contamination. With the benefit of unique perspectives gained by working across Quality, Technical and Operations Management roles at all levels within the food industry, Swainson's Handbook of Technical and Quality Management considers the very diverse remits and particular challenges of those working to assure product Quality, Safety and Legality in the sector.
Includes contributions from: Andy Bowles, Steve Clemenson, Wojciech J. Florkowski, Luanne Gounder, Fiona Houston, Colin & Lindy Jeffery, Richard F. Stier, Belinda Stuart-Moonlight, Mark Swainson, Kevin Swoffer, Colin W. Wrigley.
Keywords: Food industry and trade -- Quality control.; Food industry and trade -- Handbooks, manuals, etc.; elektronické knihy; electronic books